HUBUNGAN KEBIASAAN BEROLAHRAGA DENGAN TINGKAT STRES PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS RIAU TAHUN PERTAMA - Rony Wahyudi; Eka Bebasari; Elda Nazriati (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTPrevalence of stress occasion on medical students is pretty high, especially first grade medical students. Problems of adaptation to new environment are the most common cause of stress occuring on first grade medical students. Stress can become negative effect for individual. Various strategies of stress management were done to reduce stress, one of them was exercise. Routine exercise can reduce incidence and severity of mood disorders related to stress. This study was aimed to understand the correlation between exercise habits and stress levels on first grade medical students of Faculty of Medicine, University of Riau. This study used analytic design with cross-sectional approach. Study samples were 166 samples using total sampling technique. Data were accumulated using Medical Student Stressor Questionnaire (MSSQ) that had been modified for stress levels and exercise habits questionnaire. The obtained data were analyzed using Chi Square test and obtained a value of p=0,045 (p<0,05) that showed that there was a significant correlation between exercise habits and stress levels.Keyword: stress levels, exercise habits, first grade medical students, MSSQ